The Accounting Support of the Logistics Strategy in Business Management for Security Purposes - PYLYPENKOО.; YURCHENKOО. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The need in elaborating and implementing innovative decisions for performance enhancement of the logistics management in business enterprises has increased due to the high instability and uncertainty of business operation resulted from imposed quarantine restrictions due to the pandemic of coronavirus and fluctuations of exchange rates, which raises the importance of studies focused on improvements in the conception of accounting support of logistics operations from the business security perspective. The essence of neologistics as an innovative vector in the logistics activities is shown, with highlighting the advantages gained by business enterprises from its implementation. The authors’ framework of the accounting support for logistics operations on purchases of material assets and implementation of an innovative logistics strategy in business management for business security purposes is proposed. It is based on the three vectors of the integrated accounting support of the logistics strategy in business management: organizational vector, methodological vector, and vector of control. It is emphasized that the implementation of this framework is capable to increase the significance of criteria used in performance assessment of accounting, such as reliability, completeness, analytical relevance and timeliness of data. Factors were determined as part of this framework, allowing business enterprises that have implemented integrated planning, economic analysis, accounting and control of data processing to broaden the range of decisions on cost reduction in logistics without affecting the quality of products or services; the resulting modifications in the accounting objectives are given. It is shown how this framework, once implemented, will change the accounting practices of business enterprises pertaining to recording of logistics costs.